Dual educational rationality and acculturation in Mapuche people in Chile - Quilaqueo, Daniel; Riquelme, Enrique; Paez, Darío; Mera-Lemp, María José (Frontiers in Psychology, 2023)
Even though Mapuche people represent the largest indigenous population in Chile, the “logic of double rationality” in their educational knowledge and its link with acculturation dynamics, has been scarcely studied. The aim of this study was to explore the relationships between the attitudes toward school education and the acculturation orientations of 468 Mapuche people, with ages from 17 to 53 years (M = 16.19; SD = 7.0). Participants were students of secondary schools and universities from urban and rural areas of different regions of Chile. Results showed that most of the participants presented a bicultural orientation (39.4%), followed by a group of segregated or ethnic identity profile (23.5%), while those who preferred assimilation (17.5%), and marginalization (20.7%) represented a minority. Results indicated that people identified as bicultural scored higher in the components of dual Mapuche/ Chilean Mestizo educational rationality than the other acculturation profiles. Also, the fluency in speaking Mapuche language was positively associated with the perception of cultural differences in knowledge and education between Mapuche and Chilean culture, the evaluation of the teaching of Mapuche culture, the perception of school as a factor of assimilation, the valuation of bicultural practices, and the justification of double rationality. Findings’ contributions to the development of pertinent educational practices in contexts of social and cultural diversity are discussed.